Sistem Pakar Mendiagnosa Penyakit Lupus Menggunakan Metode Constraint Satisfaction Problem (CSP) - Jefri Amanda (STMIK Budi Darma, 2021)
At this time the use of computer peripheral technology has grown rapidly among the people. Most people use it not only for commercial purposes, but also to get information about disease detection quickly and efficiently with computer-based applications that can help the general public to find out the causes and symptoms of disease. For this reason, we need a system designed to be able to mimic the expertise of an expert in answering questions and solving problems according to the knowledge of an expert that is incorporated into a computer system. The development of artificial intelligence technology that has occurred has enabled expert systems to be applied in detecting diseases using programming languages. One of them is in providing information about various problems, especially lupus. The expert system method used is the Constraint Satisfaction Problem (CSP) which is used to deal with uncertainties in the diagnosis of lupus.